Separation of nitroaromatics from wastewater by using supported ionic liquid membranes - Bhosale, Vikas K.; Chana, Harpreet K.; Kamble, Sanjay P.; Kulkarni, Prashant S. (Journal of Water Process Engineering, 2019)
Nitroaromatics have been released into wastewater during its production and application, thus, contaminating the ecosystem. The stringent discharge limits of industrial effluents have led to the development of sustainable technologies for removal of nitroaromatics from wastewater. In the present investigation, separation of nitroaromatic compounds such as TNT, TNP and Tetryl from model wastewater was investigated by using supported ionic liquid membrane (SILM) process. Various aliquat 336 based ionic liquids (ILs) were synthesised and characterized, and immobilized in PTFE and PVDF supports for the preparation of SILMs. The key parameters such as type of IL and striping phase, feed phase pH, selectivity for SILM, extraction kinetics and reuse of SILM were studied, in detail. The size of IL-anion plays an important role in removal process. The SILM was found to be selective for TNP over other nitroaromatics. Maximum separation of TNP (< 95%) was achieved with IL, [A336][SCN] within 12 h. Selectivity and reuse of the membrane indicate the potential of SILM technology as a sustainable chemical process for the treatment of nitroaromatics contaminated wastewater.
Keywords: Ionic liquid; Membrane; Nitroaromatics; Separation; wastewater